Digital Currency Adoption: A Comparative Analysis of Global Trends and the Nigerian eNaira Digital Currency - Abdullahi, Marzuk; Ahmad, Abubakar; Pandey, Binay Kumar; Pandey, Digivijay (SN computer science, 2024)
The purpose of the present investigation seeks to take on the gaps that have been identified in digital money acceptance around the globe while carrying out a comparative study with the Nigerian eNaira digital currency through investigating the primary variables affecting the desire to adopt the eNaira digital currency within Nigeria. Digital currencies, referred to as any form of exchange traded electronically using information technology as well as the World Wide Web, are attracting worldwide recognition and are currently being utilized by authorities and central banks around the world. As of July 2020, approximately 36 central banks worldwide had announced plans to launch retail prices or wholesale Central Bank digital currencies as an aggressive response to the difficulties presented by digital currencies. Nigeria has become the first African nation to unveil its methods of national digital currency on October 25, 2021. Regardless of being Africa's first digital currency, there is currently very little written work available on eNaira acceptance in Nigeria. The IMF and the Central Bank of Nigeria have repeatedly grumbled about the limited use of technological advances, with only 700,000 consumers downloading the eNaira wallet out of over 200 million Nigerians since the currency's launch. As a result eNaira is viewed as an option for responding to some of the issues that have historically afflicted conventional means of payment within the country, such as fees that are high, slow processing times, and a shortage of utilization of financial institutions in remote regions. In conclusion this work present an obstacle as well as suggestions on digital currency adoptions, in particular the eNaira in Nigeria.